2021
DOI: 10.1503/cmaj.202303
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in office and virtual primary care during the early COVID-19 pandemic in Ontario, Canada

Abstract: BACKGROUND: Globally, primary care changed dramatically as a result of the coronavirus disease 2019 (COVID-19) pandemic. We aimed to understand the degree to which office and virtual primary care changed, and for which patients and physicians, during the in itial months of the pandemic in Ontario, Canada. METHODS: This population-based study compared comprehensive, linked primary care physician billing data from Jan. 1 to July 28, 2020, with the same period in 2019. We identified Ontario residents with at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
342
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(400 citation statements)
references
References 12 publications
25
342
1
3
Order By: Relevance
“…The ease, satisfaction, and moderate comfort in using the various existing virtual care modalities reported in this study might have facilitated the 59.9% sharp rise in adoption upon the emergence of the pandemic. Our findings are consistent with a recently published study that reported a 56-fold increase in virtual visits’ uptake during the pandemic compared to the pre-COVID-19 period [ 25 ]. The reported dramatic shift in primary care providers’ use of virtual care during the pandemic exhibits primary care’s resiliency in utilizing various virtual modalities and demonstrates a capacity to adopt simple digital tools quickly.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The ease, satisfaction, and moderate comfort in using the various existing virtual care modalities reported in this study might have facilitated the 59.9% sharp rise in adoption upon the emergence of the pandemic. Our findings are consistent with a recently published study that reported a 56-fold increase in virtual visits’ uptake during the pandemic compared to the pre-COVID-19 period [ 25 ]. The reported dramatic shift in primary care providers’ use of virtual care during the pandemic exhibits primary care’s resiliency in utilizing various virtual modalities and demonstrates a capacity to adopt simple digital tools quickly.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, in rural communities, just 45.7% of households have equal access [ 27 ]. Glazier and colleagues reported that rural residents were among those with the lowest virtual care use at 60.6% during the pandemic [ 25 ]. Another review conducted by Li and colleagues in 2020 underscored the need to address virtual care’s technical capacity in rural communities [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with housed or the general population, a recent study using ICES databases (similar data source for the present study), 22 found that during March to July 2019 (pre-COVID-19), there were on average 7.66 visits per 1000 people/day to PCPs in the province of Ontario (the setting of our study), while in our participants overall, there were on average 14.34 person-year visits (or 39.3 visits per 1000 people/day) to PCPs during 1-year pre-randomization. This finding suggests that our study population tended to accumulate more visits to PCs than the general population.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, family physician visits were down by over 50% in the first part of the pandemic. 14 Furthermore, many school immunization programs have been interrupted due to COVID-19. Indeed, we have lost the 2020-2021 vaccination years for school-aged children.…”
Section: Editorialmentioning
confidence: 99%